A Transformerless Multi-Cell Solid-State Fault Current Limiter for Medium Voltage Power System - Techama, Pantarote; Polmai, Sompob; Bunlaksananusorn, Chanin (My University, 2018)
This paper proposes a transformerless solid-state fault current limiter composed of multiple cells of single-phase bridge controlled rectifier with DC reactor and an AC reactor connected in parallel with cascaded rectifier cells performing current limiting in steady state. The proposed fault current limiter can be used in medium-voltage power system without power transformer so the system is more compact. With modular design of each rectifier cell, the construction and maintenance of the system could also be simplified. In this paper, the circuit designs, the computer simulation and the construction of the solid-state fault current limiter prototype are presented. The simulation and experimental results show that the proposed fault current limiter can operate properly.
Keywords: bridge-type FCL; distribution system; fault; solid-state fault current limiter